Simulation Analysis of Temperature Sensing Characteristics of Photonic Crystal Fiber with Gold Plated Surface - YANG Songyan; HE Wei; ZHANG Yumin; LIU Yantao; MA Siqi; YANG Jingze (Guangtongxin yanjiu, 2024)
【Objective】In order to solve the problem that it is difficult to make the temperature sensor of the Photonic Crystal Fiber (PCF) with Surface Plasma Resonance (SPR), a D-structure PCF temperature sensor is proposed. The micro-structure and arrangement of the air hole are also designed. The method of coating the polishing surface of the optical fiber with gold layer is used to stimulate the SPR of the optical fiber.【Methods】Ethanol is used as a temperature-sensitive material, and the temperature-sensitive effect is used as the temperature sensing mechanism to achieve the effect of temperature sensing. The finite element analysis method is used to simulate the thickness of the gold layer and the size of the elliptical air hole of the fiber respectively. The coupling characteristics between the core mode and the surface plasma mode are analyzed under different conditions, and the structure of the sensor is optimized.【Results】The temperature characteristics of the sensor are simulated. In the range of -80~80 ℃, the sensitivity of the sensor is 3.4 nm /℃, and the linearity is better than 0.969 63.【Conclusion】The temperature sensor designed in this paper has a wide temperature detection range, satisfactory sensitivity, and linearity, which can be used for real-time temperature monitoring in industrial, agricultural, and medical fields.